(untitled) (Historia, 2021)
The contribution of Rachel Isabella Steyn to the humanitarian aid programme in Germany after the First World War The different and sometimes difficult circumstances in which Mrs Rachel Isabella Steyn found herself after her husband, President M.T. Steyn’s death in 1916, was radically altered when she received a plea for humanitarian aid from a Netherlands humanitarian, Mrs H. Kröller, after the termination of hostilities after the First World War. This plea for the destitute children of post-war Germany was met by Mrs Steyn with dedication and innovation. She was ably assisted by a team of friends and societies in South African, and more especially her prestige as the widow of Pres. Steyn and an associate of Miss Emily Hobhouse. Miss Hobhouse as representative of the Save the Children Fund identified Leipzig in Germany as the city where the need was most acute. Mrs Steyn was not intimidated by the daunting challenge of organisational problems and working with other prominent South African women. Somehow they had to work together in order to get a grant from the Union Government. The first fund-raising effort realised over £10 000 and this effort fed over 8 000 children per day. A second fund-raising effort in 1923 did not realise similar spectacular results but rather focused on assisting laudable individual cases. In both fund-raising efforts the Free State contributed more per capita than any other province. She accepted with Miss Hobhouse, the German Red Cross Medal. She was also honoured in 1925 by the Senate of the Ruprecht Karls University in Heidelberg.